The Impact of Oil-Gas and Agriculture Exports on Energy and Consumer Non-Cyclical Sector Stock Prices in Indonesia: A Case Study of the Russia-Ukraine War - Anggita Wigiasti; Made Irma Lestari; Hidayatullah (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
The Russia-Ukraine war is one of the global conflicts that currently has a wide influence on the global economy. This certainly also affects the movement of stocks, which are one of the investment instruments. On the other hand, there are factors that also affect stock prices besides global conflicts, namely export value. Exports are known to be one of the macroeconomic factors that influences stock prices. This study aims to analyze the effect of the Russia-Ukraine war conflict on stock prices, especially the energy and consumer non-cyclical sectors by using exports as a moderating variable. The energy and the consumer non-cyclical sector were chosen because both have a large trade influence for Russia - Ukraine with the global economy. This study is a quantitative study using secondary data. Data were collected through the official websites of idx.co.id, investing.com, and bps.go.id. The data analysis method uses descriptive statistics, simple linear regression, and moderated regression analysis (MRA) tests. The results of the study showed that the Russia-Ukraine War had a significant positive effect on stock prices but changed to an insignificant effect after the addition of exports as moderating variable. Meanwhile, in the consumer non-cyclical sector, the Russia-Ukraine War produced an insignificant effect on stock prices and then had a significant negative effect after the addition of export as the moderating variable.